A Personalized Multimodal Approach to Music Recommendation for Music Therapy (International Journal of Engineering and Computer Science, 2024)
Mental health disorders and suicidality are rising among adolescents and young adults (A-YA) while rates of treatment engagement continue to remain low. Though the effectiveness of music therapy to enhance mental health is yet unknown for A-YA, the power of music to evoke emotions, facilitate communication, and promote relaxation suggests its promise. In this research study we discuss a multimodal music recommendation system which is capable of taking inputs in the form of a BFI-10 questionnaire, a series of self-view questions in the form of a survey, and an image of the user’s face in order to determine music preferences based on existing correlations between personality traits and taste in music, as an effort to make advancements in the field of music therapy.